KOMPETENSI HUMAS PADA KEPOLISIAN DAERAH SUMATERA UTARA - Rudi Silaen (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
Research is called competence public relations in regional police north sumatra ( the theory excellence in public relations in competence technical and managerial head of public relations and kasubbid poldasu ) .Research objectives is to find competence technical required in implement main task of public relations , competence managerial required in implement main task of public relations , and competence technical and managerial that needs to be improved in implementing main task of public relations . This research using the constructivism and competence of using excellence theory public relations with a qualitative approach .The result showed that technical competence of public relations city sumut in technical knowledge theory composition on understanding of photography , knowledge of elemen-elemen writing , press release , and material communication and introducing graphic design and prinsip-prinsip layout , yet excellence .The main factors the cause condition for public sector in the field of technical competence and managerial excellence not caused ineffective education and training public relations . Keyword : Excellence, technical competence, managerial competence